Recurrence of IgA nephropathy after kidney transplantation in steroid continuation versus early steroid‐withdrawal regimens: a retrospective analysis of the UNOS/OPTN database. (12th October 2017) - Leeaphorn, Napat; Garg, Neetika; Khankin, Eliyahu V.; Cardarelli, Francesca; Pavlakis, Martha
Summary: In the past 20 years, there has been an increase in use of steroid‐withdrawal regimens in kidney transplantation. However, steroid withdrawal may be associated with an increased risk of recurrent IgA nephropathy (IgAN). Using United Network of (Organ Sharing/Organ Procurement and Transplantation Network) UNOS/OPTN data, we analyzed adult patients with end‐stage renal disease (ESRD) due to IgAN who received their first kidney transplant between 2000 and 2014. For the primary outcome, we used a competing risk analysis to compare the cumulative incidence of graft loss due to IgAN recurrence between early steroid‐withdrawal (ESW) and steroid continuation groups. The secondary outcomes were patient survival and death‐censored graft survival (DCGS). A total of 9690 recipients were included (2831 in ESW group and 6859 in steroid continuation group). In total, 1238 recipients experienced graft loss, of which 191 (15.43%) were due to IgAN recurrence. In multivariable analysis, steroid use was associated with a decreased risk of recurrence (subdistribution hazard ratio 0.666, 95% CI 0.482–0.921; P = 0.014). Patient survival and DCGS were not different between the two groups. In the USA, ESW in transplant for ESRD due to IgAN is associated with a higher risk of graft loss due to disease recurrence. Future prospective studies are warranted to further address which patients with IgAN would benefit from steroid continuation.